2021
DOI: 10.1002/adfm.202011063
|View full text |Cite
|
Sign up to set email alerts
|

Stack‐and‐Draw Applied to the Engineering of Multi‐Material Fibers with Non‐Cylindrical Profiles

Abstract: Here, it is demonstrated that the stack-and-draw approach can be expanded to unusual materials association and profile geometries to generate fiber assemblies with unprecedented functionalities. This approach relies on the stacking of flat oxide glass slides into a preform, which is then thermally elongated into tens-of-meters-long ribbon fibers with preserved cross-section ratio. Fabrication methodology is introduced. In order to illustrate the versatility of the method, a panel of fibers with diverse geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Finally, a more complex sandwich-like fiber architecture is produced from the combination of Polyether sulfone and a TZN75 tellurite glass (glass composition 75 TeO 2 –20 ZnO–5 Na 2 O mol %). The preform is prepared from two rectangular glass plates and a 50 µm thick PES film using a modified stack-and-draw method 31 . SEM images of the fabricated fiber are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a more complex sandwich-like fiber architecture is produced from the combination of Polyether sulfone and a TZN75 tellurite glass (glass composition 75 TeO 2 –20 ZnO–5 Na 2 O mol %). The preform is prepared from two rectangular glass plates and a 50 µm thick PES film using a modified stack-and-draw method 31 . SEM images of the fabricated fiber are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Then, a glass preform possessing a rectangular core was fabricated using a modified stack-and-draw technique as outlined in Fig. 3 [28].…”
Section: Neodymium-doped Multimode Fiber Fabricationmentioning
confidence: 99%
“…Thermal and optical properties show linear evolution with respect to the Nd 3+ concentration, allowing fine control of the glass transition temperature and of the refractive index. Core and cladding glasses were selected based on these investigations and a rectangular-core multimode optical fiber was manufactured using a modified stack-and-draw technique recently developed by our group [28]. Thereafter, femtosecond laser pumping was employed to demonstrate the generation of a large-band spectral broadening in these newly-developed fibers thanks to self-guided nonlinear effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have shown that the well‐known stack‐and‐draw method can be applied not only for the production of cylindrical fiber geometries, but also for the development of unusual all‐glass or multi‐material elongated architectures. [ 16 ] In this section, we take advantage of the stack‐and‐draw method to prepare a rectangular‐section preform. Five vitreous tellurite glass plates (one core cane and four cladding plates) are processed and assembled to build the preform as described in Figure a–I.…”
Section: Preparation and Characterization Of Rectangular‐core Telluri...mentioning
confidence: 99%